A study on the fungi isolated from the carpeting, walls and prayer beads from the “New Mosque and Nuruosmaniye Mosque” situated in the province of Istanbul - Paça, Hanide Handan; Çolakoğlu, Günay Tülay (My University, 2017)
Mosques which are visited by many people every day, for both worship and touristic purposes, play an important role in the spread of infections in society. It is for this reason that research into the fungal concentrations found on the carpets, walls and prayer beads in mosques may prove instrumental in determining potential risks and in protecting the health of visitors. The sampling of fungus content from the carpeting, walls and prayer beads of two different mosques in the province of Istanbul was undertaken with the aim of determining fungi content and levels at two chosen stations in 2015 in the months of January, April, July and October. Samples were taken using dry sterile swabs. The samples brought to the laboratory were cultivated in Peptone-Dextrose Agar in appropriate conditions. The isolated fungi were spot cultivated in Malt Extract Agar (MEA) medium and pure colonies were detected. The preparations extracted from the pure culture of the fungi were examined using a microscope. In the sampling carried out for a duration of four months, 190 colonies were detected. As a result of the study undertaken, 18 different species from 8 genera were isolated. The genera identified were as follows; Alternaria, Aspergillus, Chaetomium, Cladosporium, Penicillium, Scopulariopsis, Trichoderma and Ulocladium. Amongst the genera, the 3 most commonly detected ones were; Aspergillus, 53.2% Penicillium 24.2% and Cladosporium, 14.2%. As a result of the study, the species most isolated, in order, are as follows: Aspergillus fumigatus at 25.8% Aspergillus flavus at 12.7%, Aspergillus parasiticus at 10%, Cladosporium sphaerospermum and Penicillium palitans at 8.4% respectively, Penicillium citreonigrum at 7.4%, Cladosporium cladosporioides at 6.3%, Penicillium citrinum at 5.8%, Chaetomium globosum at 4.2%, Aspergillus niger at 3.2%, Penicillium solitum and Trichoderma longibrachiatum at 1.6% respectively, Alternaria citri, Emericella nidulans and Penicillium chrysogenum at 1.05% respectively and Aspergillus sydowii, Scopulariopsis brevicaulis and Ulocladium alternariae at 0.5% respectively.
Keywords: Aspergillus; Penicillium; Fungus; Carpeting; Mosque; Indoor; Biology; Microbiology; Epidemiology; Istanbul